Dyskinesia-hyperpyrexia syndrome in Parkinson's disease triggered by overdose of levodopa — a case report and literature review - Du, Xiangnan; Wang, Xuemei; Geng, Xiaokun (Frontiers in Neurology, 2024)
Dyskinesia-hyperpyrexia syndrome, a rare medical emergency in Parkinson's disease, is first described in 2010. It is characterized by severe continuous dyskinesia associated with rhabdomyolysis, hyperthermia and subsequent alteration of the mental state. Gradual reduction of dopaminergic dose or DBS is recommended treatment. The prognosis is usually good, but sometimes fatal. But so far, this potentially fatal complication is not widely recognized by clinicians. In emergency, if clinicians fail to make prompt diagnosis and treatment, patients' conditions may get worse, and their lives may be threatened in serious cases.